10 GHz inverter‐type‐time‐amplifier based phase noise filter with −133 dBc/Hz phase noise sensitivity. Issue 11 (1st May 2018) - Hao, S.; Hu, T.; Gu, Q.
Abstract : This Letter presents an inverter‐type time amplifier (TA)‐based phase noise filter (TAPNF) with 8 dB phase noise suppression and −133 dBc/Hz phase noise sensitivity at 1 MHz offset. The phase noise improvement strategy, low noise TA design and power consumption reduction techniques are presented. The TAPNF is fabricated in a 65 nm CMOS process with 1.4 mm × 1.6 mm chip area and consumes 50 mW power. To authors' best knowledge, the TAPNF achieves the best phase noise and figure‐of‐merit compared with state‐of‐the‐arts with similar technologies and carrier frequencies.